Skate fishery and some biological aspects of fivespecies of skates off Mumbai - Raje, Sadashiv Gopal (Indian Journal of Fisheries, 2011)
Skate landings as bycatch of trawlers at Mumbai declined from 1204.4 t in 1989to 194.6 t in 2003, with an average annual landing of 334.8 t, at a catch rate of248 kg/hr. The fishing pressure has reached optimum level, which is evidencedby a decline in catch and catch rate of skate population. Rhynchobatus djiddensis(93.2%) was the most dominant species, which landed throughout the year.Infomations on the biology of five species Rhynchobatus djiddensis, Rhinaancylostoma, Rhinobatus granulatus, Rhinobatus obtusus and Rhinobatusannandalei are presented.